Filosofia e teatro à luz do pensamento benjaminiano: alegoria barroca, interrupção brechtiana e teatro pós-dramático - Altieri, Maria Silvia (2010)
The objective of this dissertation is to study the concepts of baroque allegory and Brechtian break in the light of Benjamin's thought, in order to understand the closeness that these concepts establish between the fields of philosophy and theater art through the concept of Darstellung (presentation / exposure). The proximity between theater and philosophy in Benjamin's thought is therefore, the question that guides this research and our hypothesis is that the concept of Darstellung (presentation / exposure) is the key to the elucidation of this question. Moreover, the study of the concept of allegory will be conected to the analysis of contemporary theater, specifically the concept of post-dramatic. Allegory is the link of the union betwen German Baroque drama, Brechtian theater and post-dramatic theater. The present study is not based on a linear and diachronic historical chronology. This is the synchronic sense in which the cutting was done in reverse, to use the words of Walter Benjamin. The dissertation will follow the following breakdown: the cut in the first chapter will be the study of the concept of allegory of the German Baroque drama and of the spectacle of this drama, in the second chapter I will study the Brechtian concept of interruption and the spectacle of Brechtian theater, in the third chapter the focus will be the concept of post-dramatic theater and the spectacle of this theater. The axis of this analysis and of the three chapters will be the relationship between theater and Benjamin philosophy by the key concept of Darstelung. Finally, in the final considerations the consequences of this study will be analyzed in order to open issues that may expand the vision of theater and the relationship between theatrical art and philosophy to the contemporary perspective